2013
DOI: 10.1002/lt.23753
|View full text |Cite
|
Sign up to set email alerts
|

Identification of liver transplant candidates with hepatocellular carcinoma and a very low dropout risk: Implications for the current organ allocation policy

Abstract: It has been shown that patients with hepatocellular carcinoma (HCC) meeting UNOS T2 (Milan) criteria are advantaged compared to patients without HCC under the current organ allocation system for liver transplant (LT). We hypothesize that within T2 HCC, there is a subgroup with a low risk of waitlist dropout, and should not receive the same listing priority. This study evaluated 398 consecutive patients with T2 HCC listed for LT with MELD exception from 2005 to 2010 at our center. Competing risk (CR) regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
136
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 34 publications
(69 reference statements)
14
136
3
2
Order By: Relevance
“…However many LT institutions treat most of the patients within the waiting list, since the actual time to LT may be unpredictable, and this strategy has demonstrated a favourable cost-effect balance [73] . The radiological response to bridging therapy may also help to assess the HCC biological behavior [74][75][76] , and to prioritize HCC patients for LT [77][78][79][80][81] . Patients with tumour growth beyond Milan criteria after locoregional therapies should not undergo LT.…”
Section: Waiting List Management and Bridging Therapymentioning
confidence: 99%
“…However many LT institutions treat most of the patients within the waiting list, since the actual time to LT may be unpredictable, and this strategy has demonstrated a favourable cost-effect balance [73] . The radiological response to bridging therapy may also help to assess the HCC biological behavior [74][75][76] , and to prioritize HCC patients for LT [77][78][79][80][81] . Patients with tumour growth beyond Milan criteria after locoregional therapies should not undergo LT.…”
Section: Waiting List Management and Bridging Therapymentioning
confidence: 99%
“…HCC exception point recipients with a single tumor that has a complete response to loco-regional therapy and a low alpha-fetoprotein has exceedingly low risks of waitlist dropout, suggesting that these patients should receive fewer exception points or upgrades at longer intervals. 16 Second, the full impact of the growing number of HCC exception patients on the broader waitlist population is unknown. With increasing numbers of patients receiving exception points, the mean MELD score needed to receive an organ offer also continued to increase.…”
Section: Introductionmentioning
confidence: 99%
“…A patient with a single 2 cm HCC that responds well to loco-regional therapy would likely have a much different risk of tumor progression than a patient with three tumors, each 2cm in size, with persistent viability after two treatment cycles. 16 Yet both would be awarded the same number of points as each are within Milan criteria.…”
Section: Introductionmentioning
confidence: 99%
“…In the original article, Mehta et al 2 identified a specific cohort of hepatocellular carcinoma (HCC) patients with T2 tumors whose risk of wait-list dropout was very low, and they suggested that such patients should not receive the same allocation advantage as higher risk groups (ie, those not meeting their criteria). In our editorial, we raised the issue of whether using such data to inform a new allocation algorithm might lead to worsening outcomes through the selection of recipients with a higher risk of tumor recurrence for liver transplantation (LT).…”
Section: To the Editorsmentioning
confidence: 99%